2020
DOI: 10.1111/jgh.15161
|View full text |Cite
|
Sign up to set email alerts
|

Relation of geriatric nutritional risk index with clinical risks in elderly‐onset ulcerative colitis

Abstract: Background and AimWorldwide increasing aging societies have many elderlies with intractable diseases including ulcerative colitis (UC). Reportedly, each patients' frailty as well as chronological age is a clinical risk factor of elderly‐onset UC (EOUC). Because malnutrition is one of the major manifestations of frailty, we aimed to investigate the effect of malnutrition on the prognosis of EOUC with geriatric nutritional risk index (GNRI), a prognostic tool for several diseases in the elderly to estimate malnu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…Due to the progress of treatment, patients over 60 years of age constitute an increasing population of IBD patients. Higashiyama et al suggested that the risks of hospitalization and surgery were elevated as age advanced [ 28 ]. Moreover, UC is diagnosed more and more often in the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the progress of treatment, patients over 60 years of age constitute an increasing population of IBD patients. Higashiyama et al suggested that the risks of hospitalization and surgery were elevated as age advanced [ 28 ]. Moreover, UC is diagnosed more and more often in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the value of geriatric nutritional risk index negatively correlated with disease activity, could distinguish severe activity and discriminate the elderly-onset UC patients suffering from surgery and hospitalization. Researchers proposed that malnutrition estimated by geriatric nutritional risk index was significantly related with poor clinical courses of the elderly-onset UC patients, suggesting that the evaluation of nutritional status at the onset might be useful for predicting risks of clinical courses [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…GNRI is a general indicator that evaluates the nutritional status of patients, that is, it is an effective and simple risk indicator reflecting the nutritional risk of patients, and has been proven as a predictor of hospitalized elderly patient prognosis 12 . GNRI is based on serum albumin and weight loss measurements, which are strong independent risk factors for mortality in elderly persons 19 . GNRI can also classify elderly patients according to morbidity and mortality risks in relation to pathologies often associated with malnutrition 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional deficiency and malnutrition are well documented in ageing populations and a diagnosis of IBD, with associated malabsorption, impaired appetite and unpleasant symptoms, may increase this risk [7,39,40]. Furthermore, studies suggest that malnutrition may contribute to worse outcomes in patients with older-onset IBD [6,8,41,42] (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…1). Thus, although IBD dietary guidance suggests limiting the intake of animal protein, complete avoidance of protein-rich dietary components, such as meat and dairy products, may increase the risk of sarcopenia and its associated complications in more frail, elderly people [8,13,40,43]. Similarly, adequate intake of dietary fibre is recommended in those with IBD and its avoidance has been linked with adverse medical outcomes in older adults such as colorectal cancer and cardiovascular disease [13,14,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%